Tobacco nuclear gene for the 31 kd chloroplast ribonucleoprotein: genomic organization, sequence analysis and expression. - Li, Y Q (1991)
We have previously identified three chloroplast ribonucleoproteins and characterized their cDNAs. Here we present the genomic organization, sequence and expression of one of their genes. The 31 kd ribonucleoprotein (cp31) from tobacco (Nicotiana sylvestris) chloroplasts is coded for by a single-copy nuclear gene. This gene was isolated and its sequence was determined. The gene contains four exons and three introns. The position of its first intron is conserved among the genes for the maize abscisic acid-induced glycine-rich protein, the human hnRNP A1 protein and cp31. The transcription start site was determined to be 168 bp upstream from the translational initiation codon in both leaf and root tissues. No alternatively spliced transcripts was detected, suggesting that a diversity of chloroplast ribonucleoproteins is generated probably by gene amplification rather than alternative splicing.